Anchoring of a nickel Schiff base complex with mixed ligands on MCM-41 as a heterogeneous catalyst for the synthesis of quinoxaline derivatives by various energies. (1st January 2023) - Bharathi, M.; Mathivathani, S.; Indira, S.; Vinoth, G.; Christopher Leslee, Denzil Britto; Shanmuga Bharathi, K.
Graphical abstract: A new mixed ligand Ni-Schiff base complex was designed and appended on MCM-41. The hexagonal honeycomb-like channel of MCM-41 was maintained upon immobilization. Synthesis of quinoxaline derivatives under a green path. The Ni-MCM-41 catalyst showed stability upon successive reuse for up to four cycles. Abstract: A new class of heterogeneous catalyst, a nickel Schiff base complex of mixed ligands on MCM-41, has been synthesized. The Ni-MCM-41 catalyst has been characterized by FT-IR, PXRD analysis, N2 adsorption and desorption, elemental mapping-EDX, SEM and TEM microscopy, ICP-OES, TGA and 13 C-CP-MAS-NMR. The catalyst was used for the green synthesis of quinoxaline derivatives via a simple condensation through thermal heating, ultrasonication and microwave irradiation. This environmentally benign method provides several advantages, such as mild reaction conditions, short reaction time, excellent yield of up to 99 %, operational simplicity, catalyst stability, heterogeneous nature and easy retrievability of the catalyst by filtration. The catalyst can be reused for up to four cycles without significant deterioration in the catalytic activity. The effectiveness of the energy sources for the synthesis of quinoxalines is as follows: microwave irradiation > ultrasonication > thermal heating. The efficiency of our catalyst is also compared against literature reports and the results are discussed.